ENHANCING PRODUCTION EFFICIENCY IN A HOME-BASED TEMPE CHIPS INDUSTRY - Latifatul Ummi Qurrota'ayun; Muhamad Zainudin; Siti Nur Mahmudah (JURNAL PROFIT, 2024)
Management is the process of coordinating the resources owned by a company to achieve goals. Management has five functions, namely, planning, organizing, actuating, and controlling. Home industry is a company whose family members are directly involved in the ownership and position or function. Home Industry is characterized by the ownership or other involvement of two or more family members in the same role in the life and functioning of the business. This research was conducted to determine the application of production management for the tempe chips home industry,including: planning, organizing, actuating, and controlling, as well as the impact of the application of production management on the development of the tempe chips home industry. Based on the research results, the implementation of production management in the home industry has been running optimally as evidenced by theimplementation of the four management functions namely planning, organizing, actuating/implementing and controlling. The impact of implementingproduction management on the development of this home industry is increasingprofits, increasing orders, achievingproduction targets thatcan meetmarket needs, aswell as the addition of networksthat work together with the Berkah Jaya Tempe Chips Home Industry. Manajemen merupakan proses pengkoordinasian sumber daya yang dimiliki oleh sebuah prusahaan untuk mencapai tujuan. Manajemen mempunyai lima fungsi yaitu, planning, organizing, actuating ,dan controlling. Home industry adalah sebuah perusahaan yang anggota keluarganya secara langsung terlibat di dalam kepemilikan dan jabatan atau fungsi. Home Industry merupakan karakteristik dengan kepemilikan atau keterlibatan lainnya dari dua peran atau lebih anggota keluarga yang sama dalam kehidupan dan fungsi bisnisnya. Penelitian ini dilakukan untuk mengetahui penerapan manajemen produksi home industry keripik tempeberkah jaya meliputi: planning, organizing, actuating, dan controlling, serta dampak dari penerapan manajemen produksi terhadap perkembangan home industry keripik tempe berkah jaya. Berdasarkan hasil penelitian, penerapan manajemen produksi pada home industry sudah berjalan secara optimal dibuktikan dengan adanya penerapan empat fungsi manajemen yaitu perencanaan,pengorganisasian,penggerakan/pelaksanaan dan pengendalian. Dampak dari penerapan manajemen produksi terhadap perkembangan home industry ini adalah meningkatnya keuntungan yang diperoleh, meningkatnya pesanan, tercapainya target produksi yang dapat memenuhi kebutuhan pasar, serta adanya penambahan jaringan yang bekerja sama dengan home industry Keripik Tempe Berkah Jaya.